Molecular mechanics of caffeic acid in food profilin allergens - Barazorda-Ccahuana H.L. (2019)
Vegetable profilins are considered potent allergens for their cross-reactivity as a result of the high sequence identity. Nowadays an attractive attention is focused to find new ligands to inhibit the active site of allergenic profilins. Some studies have shown that caffeic acid may have a certain inhibitory effect on some allergens. For this reason, we studied caffeic acid as an important ligand and its interaction between seven vegetable profilins. We applied molecular dynamic simulations methods and binding free energy analysis by MM–PBSA. We found that caffeic acid had a favorable behavior, and their coupling was mediated by hydrophobic interactions. Furthermore, the analysis of epitopes showed an important contribution of the secondary structure after docking simulations. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.